Coping With Water Supply Shortages in Major Cities of Malawi - Mpakati-Gama, Effiness C.; Mkandawire, Theresa (Universitas Indonesia, 2015)
Urban water shortages continue to pose a threat to the livelihoods of many people in most developing countries including Malawi. In the past few decades, researchers and policy makers have focused on improving the performance of water utility infrastructure in order to eliminate this threat. However, little efforts have been made to understand social issues to water shortage and how people respond to them. Using a cross sectional survey and interviews in 11 townships in three cities of Malawi, the water supply disruptions and the study population’s coping mechanisms to water shortage and frequent disruptions were investigated. This study aimed at understanding water shortage coping mechanisms and the implication on the income and health of the affected populations. The results suggest that while some people in areas affected by water disruptions spend huge sums of money to get water from alternative sources, others are exposed to health hazards. That is, circumstances force them to draw water from unsafe sources, hence, exposing themselves to diseases. The results imply that there is an urgent need to address water supply systems in order to prevent people from impoverishment and water borne diseases.